Discrete-time super-twisting observer with implicit euler method - Xiong X.; Liu Z.; Kamal S.; Jin S. (My University, 2025)
This brief proposes a new discrete-time realization of the super-twisting algorithm based observer. While keeping the property of chattering suppression, the estimation precision of the proposed realization scheme is consistent with the continuous-time super-twisting algorithm (STA), that is, in the absence of noises, the estimation errors satisfy the standard asymptotical accuracy level, i.e., |e1| ∼ μ 1h2 and |e2|∼ μ 2h with sampling time h and two positive constants μ 1 and μ 2. Comparing to the conventional explicit Euler method, the proposed scheme is more exact in the term of smaller constants μ 1 and μ 2. The superiority of the proposed scheme is demonstrated through an example of typical buck converter circuit system. © 2004-2012 IEEE.